Implementation of Village Financial Management Policy - Yosya Rizal; Fernandes Simangunsong; Sampara Lukman; Ali Hanafiah Muhi (Yayasan Riset dan Pengembangan Intelektual, 2024)
There is still a lack of competence of the Human Resources machinery of the village financial managers in the district of Pesawaran and there is no technical regulation at the District level as the guidelines that refer to the implementation of village financial management, resulting in delays in the establishment of the APBDesa, delay in the proposal for the distribution of village funds, and low absorption and use of villages funds in the District of Pasawaran. The purpose of this research is to analyze the implementation of the village financial management policy in the district of Pesawaran Province of Lampung. To analyze the implementation of rural financial management policies in the district of Pesawaran Province of Lampung, researchers used Hamdi's public policy implementation theory consisting of productivity, linearity, and efficiency. The method used in this research is descriptive research with a qualitative approach, namely by describing and analyzing the implementation of the Village Financial Management Policy in the district of Pesawaran Province of Lampung. As for the data-gathering techniques used are interviews, observations, and documentation. The results of the research show that the implementation of the village financial management policy in the district of Pesawaran Province of Lampung has not been fully implemented efficiently, linearly, and productively. This is due to the non-implementation of the financial management procedures of the village regulated in the Peremendagri Number 20 Year 2018 and the Perbup district of Pesawaran Number 55 Year 2018 by the Government of the district. So then the researchers found that the government of the district of Pesawaran district to make the Bupati Regulations related to the technical guidelines for the preparation of APBDes so that the implementation of village management from the beginning of the planning phase, until responsibility can run in a transparent, accountable, and implemented in an orderly and budget discipline.